2005
DOI: 10.1539/joh.47.242
|View full text |Cite
|
Sign up to set email alerts
|

A 13‐Week Toxicity Study of Bismuth in Rats by Intratracheal Intermittent Administration

Abstract: A 13-Week Toxicity Study of Bismuth inRats by Intratracheal Intermittent Administration: Yuri SANO, et al. Department of Preventative Medicine and Public Health, School of Medicine, Keio University-Although bismuth is widely used as a lead substitute in the industrial field, the toxicity of bismuth by inhalation is little known. We performed a 13-wk intratracheal intermittent bismuth dose toxicity study. Bismuth was administered at dose levels of 0, 0.8, 4, 20 mg/kg to male Crj:CD(SD)IGS rats (SPF) by intratra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…MCV and MCHC are closely related to an adequate supply of Fe to hemoglobin [ 13 ], [[22]. It is established that the target site of bismuth in protein and enzymes are both Fe sites and Zn sites [23].Bismuth also binds to serum transferrin, transferrin are functional in iron transport to cell from blood [24].The chronic toxic action of the metals probably depresses the proliferative activity of the stem cells [3].The WBC of experimental animals used in this study was significantly low .It is recorded that changes in surface markers of stem cell were remarkable in mice exposed to heavy metal [12].The alteration of blood parameters of mammals is in agreement with the increasing of heavy metal dose [26], [27]. The higher value of alanine aminotransferase The dose independent changes of bismuth chloride in serum enzymes of Sprague Dawley rats were observed a 3 day Experiment because the exposure to bismuth chloride lead to inflammation and nicrosis hepatic cells of liver and them increases in liver inzymrs [10,11].…”
Section: Methodsmentioning
confidence: 99%
“…MCV and MCHC are closely related to an adequate supply of Fe to hemoglobin [ 13 ], [[22]. It is established that the target site of bismuth in protein and enzymes are both Fe sites and Zn sites [23].Bismuth also binds to serum transferrin, transferrin are functional in iron transport to cell from blood [24].The chronic toxic action of the metals probably depresses the proliferative activity of the stem cells [3].The WBC of experimental animals used in this study was significantly low .It is recorded that changes in surface markers of stem cell were remarkable in mice exposed to heavy metal [12].The alteration of blood parameters of mammals is in agreement with the increasing of heavy metal dose [26], [27]. The higher value of alanine aminotransferase The dose independent changes of bismuth chloride in serum enzymes of Sprague Dawley rats were observed a 3 day Experiment because the exposure to bismuth chloride lead to inflammation and nicrosis hepatic cells of liver and them increases in liver inzymrs [10,11].…”
Section: Methodsmentioning
confidence: 99%
“…For bismuth inhalation tests, the half‐lives of Bi clearance from the lungs were found to be 4.47, 3.25, and 2.10 days at doses of 20, 100, and 500 mg kg −1 , respectively, thereby suggesting that foreign body inflammation occurs in the lungs. [ 78 ] However, no serious changes were observed in the other organs. Therefore, it was concluded that Bi serves as a metallic substance with low toxic effects under the conditions tested in this study.…”
Section: Specific Toxicity Study Of Liquid Metalmentioning
confidence: 99%
“…[76] A systematic understanding of biocompatibility is important in this case. Sano et al [77,78] conducted a series of animal experiments to evaluate Bi toxicity. In their study, the underlying toxicity of Bi was characterized by monitoring the health of rats 14 days after oral administration of 2000 mg kg −1 Bi.…”
Section: Bi and Its Alloysmentioning
confidence: 99%
“…Among heavy metals, bismuth is unique due to its much lower toxicity than that of its neighbors in the periodic table such as lead, thallium, and antimony. In fact, bismuth has been widely used as a lead substitute in industries,13, 14 because the toxicity of bismuth and its salts is dose‐dependent and only large doses can be fatal 15–17. Furthermore, the existence of insignificant amounts of bismuth in the ENP deposit surface does not undermine its corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%